Autism, females, and the DSM-5: Gender bias in autism diagnosis. Issue 4 (3rd July 2016) - Haney, Jolynn L.
ABSTRACT: Autism is a neurodevelopmental condition thought to occur predominantly in males. Despite limited research, there is evidence that criteria used to identify autism are gender-biased, leaving females with autism undiagnosed or misdiagnosed. This article provides a brief history of autism and an overview of research related to gender bias in autism spectrum diagnosis. In addition, research on DSM-5 autism criteria relevant to gender is reviewed, along with the role diagnostic screening instruments play in perpetuating gender bias. Finally, the sensitivity of DSM- 5 criteria to females on the autism spectrum is considered within the context of social work practice and research.